KOMUNIKASI PEMBELAJARAN DARING PADA MAHASISWA INTROVERT AKMRTV JAKARTA - Hanif Abdullah; Noviawan Rasyid Ohorella; Edy Prihantoro (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the communication of online learning to introverted students in communicating themselves during online learning during the COVID-19 pandemic. With online learning, introverted students learn using social media such as Zoom Meeting, Google Meet, Whatsapp Group, and others. The research method used in this study is a qualitative descriptive method. The data used in this study consisted of primary data and secondary data. Primary data in the form of information obtained from interviews with several informants. While secondary data in the form of data obtained from books and other sources. The theory used in this scientific writing research is interpersonal theory, where with this theory we can find out the communication between the communicant and the communicator. The data collection techniques used were observation, interviews, and documentation, where the researcher tried to obtain comprehensive information from the informants. Based on the results of the study, the online learning communication experienced by introverted students was considered appropriate. Communication of online learning to introverted AKMRTV students is through online learning media which is desired to get very good results between lecturers and students.